A Gallus gallus Model for Determining Infectivity of Zoonotic Campylobacter - Lye, Dennis; Struewing, Ian; Gruber, Theresa M.; Oshima, Kevin; Villegas, Eric N.; Lu, Jingrang (Frontiers in Microbiology, 2019)
To better understand public health implications of waterfowl as reservoirs for zoonotic sources of Campylobacter in recreational waters, we developed a Gallus gallus (chick) model of infection to assess the pathogenicity of environmental isolates of Campylobacter. This method involved exposure of 1-day-old chicks through ingestion of water, the natural route of infection. Viable Campylobacter from laboratory-infected animals were monitored by using a modified non-invasive sampling of fresh chick excreta followed by a passive polycarbonate-filter migration culture assay. The method was used to evaluate the infectivities of three laboratory strains of Campylobacter spp. (C. coli, C. jejuni, and C. lari), three clinical isolates of C. jejuni, and four environmental Campylobacter spp. isolated from California gulls (Larus californicus). The results revealed that chicks were successfully infected with all laboratory and clinical isolates of Campylobacter spp. through ingestion of Campylobacter-spiked water, with infection rates ranging from <10% to >90% in a dose-dependent manner. More importantly, exposure of chicks with Campylobacter spp. isolated from Gallus gallus excreta also resulted in successful establishment of infection (≤90%). Each monitored Campylobacter spp. contained ≥7.5 × 104 CFU∙g-1 of feces 7 days post-exposure. These results suggest that a Gallus gallus model can be used to assess infectivity of Campylobacter isolates, including gull and human clinical isolates. Use of an avian animal model can be applied to assess the importance of birds, such as the Gallus gallus, as potential contributors of waterborne-associated outbreaks of campylobacteriosis.